الأبعاد الثقافية للصورة الإشهارية المتحركة - بوفرمة, سهيلة (كلية العلوم الإجتماعية لجامعة مستغانم, 2024)
تندرج دراستنا متمثلة في الأبعاد الثقافية للصورة الإشهارية المتحركة دراسة تحليلية سيميولوجية لعينة من الإعلانات الإشهارية المتحركة في التلفزيون الجزائري ضمن الدراسات التحليلية التي تعني باهتمام كبير من طرف الباحثين وكان الإشكال المطروح في هذخ الدراسة هو معرفة الأبعاد الثقافية للصورة الإشهارية المتحركة اعتمدان عللى منهج التحليلي الكيفي السيولوحي لانه الأنسب يمثل هذه الرداسات ومن بين المناهج التي تساعد نا على تحليلي الومضات الشهارية التلفزيونية ,بالأخص عندما نضع بالحسبان أن الصورة الإشهارية التلفزيونية هي من بين أكثر الصور التي تحمل الرموز والدلائل ,كما استخدمنا أداة الملاحظة نظرا للملائمة هذه الأخيرة للطبيعة الدراسة عن طريق الملاحظة بالصدفة خيث أثناء التعرض لبرامج التلفزيون الجزائري ,للاحظنا أن بعض الومضات الإشهارية التي تبث تحمل في مضمونها معاني ودلالات سيمولوجية ومن ثم فإن الفضول للمشاهدة كل الومضات الإشهارية التي تبث في القنوات التلفزيونية وملاجظتها علميا من أجل استخراج جميع المضامين الخفية التاي تحملها خذه الإشهارات ,كما اعتمدنا كذلك على مقاربة رولان بارت في تحليلي الصورة الإشهارية التلفزيونية كأداة للتحليل الرموز ,وجاءت عينة الدراسة قصدية متمثلة في ومضة اشهارية للمنتوج غذائي ,ماء زخر القصبة وقد تم تقسيم الدراسة الى اطاؤين منخجي وتطبيقي وفضول نظرية تمثلت في فصلين الأول متعلق بالإشهار التلفزيوني والصورة الإشهارية والثاني خاص كيفية تصميم الرسالة الغشهارية وتم توصل الى مجموعة من النتائج تتلخص في أن الومضات الإشهارية الجزائرية تحمل أبعاد ثقافية عديدة تعبر عن طبيعة المجتمع الجزائري وبيئته الإجتماعية المحافظ عليها من هلال ارتباطه بالعادات والتقاليد والثقافة المتنوعة التي تزخر بها والعمل على الحفاظ على هذه القيم وتداولها عبر الأجيال
دراسة سيمولوجية لوضمة اشهارية على قناة سميرة TV
Our study, represented by the cultural dimensions of the animated advertising image, a semiological analytical study of a sample of animated advertising advertisements on Algerian television, falls within the analytical studies that are concerned with great interest by researchers. The problem raised in this study was knowing the cultural dimensions of the animated advertising image. We relied on the qualitative analytical method because it is the most appropriate to represent these traces and is among the methods that help us to analyze television advertising flashes, especially when we take into account that the television advertising image is among the images that most carry symbols and evidence. We also used the observation tool due to the latter’s suitability to nature. Study by chance observation. During exposure to Algerian television programs, we noticed that some of the advertising flashes that are broadcast carry in their content semiological meanings and connotations. Hence, the curiosity to watch all the advertising flashes that are broadcast on television channels and observe them scientifically in order to extract all the hidden contents that they carry is taken by the advertisements. We also relied on the approach of Roland Barthes in analyzing the television advertising image as a tool for analyzing symbols. The sample of the study was intentional, represented by an advertising flash for a food product, water from the grapefruit. The study was divided into two sections, methodological and applied, and theoretical curiosity, which was represented in two chapters, the first related to television advertising and the advertising image. The second is specific to how to design the fraudulent message A set of results were reached, which are summarized in the fact that Algerian advertising flashes carry many cultural dimensions that express the nature of Algerian society and its social environment, preserved by its connection to the diverse customs, traditions and culture with which it abounds, and work to preserve these values and circulate them across generations.
Keywords: الصورة الإشهارية .الومضة .الابعاد الثقافية